An Overview of the Protein Binding of Cephalosporins in Human Body Fluids: A Systematic Review - Jongmans, C.; Muller, A. E.; Van Den Broek, P.; Cruz De Almeida, B. De Melo; Van Den Berg, C.; Van Oldenrijk, J.; Bos, P. K.; Koch, B. C. P. (Frontiers in Pharmacology, 2022)
Introduction: Protein binding can diminish the pharmacological effect of beta-lactam antibiotics. Only the free fraction has an antibacterial effect. The aim of this systematic literature review was to give an overview of the current knowledge of protein binding of cephalosporins in human body fluids as well as to describe patient characteristics influencing the level of protein binding. Method: A systematic literature search was performed in Embase, Medline ALL, Web of Science Core Collection and the Cochrane Central Register of Controlled Trials with the following search terms: “protein binding,” “beta-lactam antibiotic,” and “body fluid.” Only studies were included where protein binding was measured in humans in vivo. Results: The majority of studies reporting protein binding were performed in serum or plasma. Other fluids included pericardial fluid, blister fluid, bronchial secretion, pleural exudate, wound exudate, cerebrospinal fluid, dialysate, and peritoneal fluid. Protein binding differs between diverse cephalosporins and between different patient categories. For cefazolin, ceftriaxone, cefpiramide, and cefonicid a non-linear pattern in protein binding in serum or plasma was described. Several patient characteristics were associated with low serum albumin concentrations and were found to have lower protein binding compared to healthy volunteers. This was for critically ill patients, dialysis patients, and patients undergoing cardiopulmonary bypass during surgery. While mean/median percentages of protein binding are lower in these patient groups, individual values may vary considerably. Age is not likely to influence protein binding by itself, however limited data suggest that lower protein binding in newborns. Obesity was not correlated with altered protein binding. Discussion/Conclusion: Conclusions on protein binding in other body fluids than blood cannot be drawn due to the scarcity of data. In serum and plasma, there is a large variability in protein binding per cephalosporin and between different categories of patients. Several characteristics were identified which lead to a lower protein binding. The finding that some of the cephalosporins display a non-linear pattern of protein binding makes it even more difficult to predict the unbound concentrations in individual patients. Taken all these factors, it is recommended to measure unbound concentrations to optimize antibiotic exposure in individual patients. Systematic Review Registration: PROSPERO, identifier (CRD42021252776).